A questão epistemológica da formação de professores no curso de pedagogia: a ciência da educação entre a teoria pedagógica e o praticismo - Adelson Ferreira da Silva (2022)
This doctorate thesis is bound to the field of teacher training and aims to answer the following research question: which epistemological presuppositions give basis to the training in Pedagogy at Bahia State University, and which is the position of teacher experience at the field of epistemological disputes traditionally consolidated on the courses' pedagogical-curricular projects? We start from the principle that an analysis of the Pedagogical-Curricular Project of the Pedagogy Course offered by this university and, at the same time, the research with egresses that have obtain their initial training on the afore mentioned course can point out possibilities of more fecund dialogues and of less hierarchical positions between pedagogy epistemology, education science, pedagogical theory and the experience built into the exercise of teaching. It is a qualitative research that uses the following devices for data generation: 1) documentary analysis; 2) structured questionnaire; and 3) interview. The data analysis is based on the methodological framework of content analysis, working with the categorical-thematic technique of meaning unities contained at the discourse of the subjects and at the documents, seeking to evince the qualitative aspects of the research object (BARDIN, 2016). It counts stills on the epistemic support of philosophical hermeneutics (GADAMER, 2015), in order to broaden the horizon of understanding of the interpretative context coded by the categorization process. The theoretical framework includes authors from the education field, among which stand out: Apple (2003, 2008), Charlot (2002), Franco (2008), Gatti (2010), Gauthier (2013), Libâneo (2006, 2010, 2012), Pimenta (2011), Saviani (2013); from epistemology field, such as: Gadamer (2001, 2002, 2015), Habermas (2014), Husserl (2012); and of others that has opened possibilities of investigative interfaces between pedagogy and epistemology. The results evinced that, with the advance of the neoliberal rationality, of management culture, and of the application of the economicist logic at the education field and teacher training, reassure pedagogy as an education science is a way to ground in more consistent bases its epistemology, its scientificity status and its epistemic autonomy at the domain of pedagogical knowledge. We also verified that the Resolutions CNE/CP nº 1/2002, CNE/CP nº 1/2006, CNE/CP nº 2/2015 and CNE/CP nº 2/2009 have instituted guidelines that advanced little in terms of a contribution to the epistemological question of pedagogy and the valuation of pedagogical theory as foundation of teacher training; and that the thesis of teaching as basis of the training in Pedagogy subordinates the pedagogical rationality to its professional activity, making concessions to practicism, to pedagogical dogmatism and to the pragmatic incursions coming from the corporative world. They also show the need to institute the Pedagogy Epistemology as curricular matter and branch of pedagogical science.